PH‐Triggered Size‐Tunable Silver Nanoparticles: Targeted Aggregation for Effective Bacterial Infection Therapy. Issue 22 (2nd May 2022) - Cheng, Xinting; Pei, Xibo; Xie, Wenjia; Chen, Junyu; Li, Yuanyuan; Wang, Jian; Gao, Huile; Wan, Qianbing
Abstract: The rapid spread of drug‐resistant pathogens threatens human health. To address the current antibacterial dilemma, the development of antibiotic‐free strategies using nanotechnology is imperative. In this study, silver nanoparticles (Ag‐P&C NPs) with pH‐sensitive charge reversal and self‐aggregation capacities are successfully synthesized. In the acidic microenvironment of bacterial biofilms, protonation of the surface peptide enhances the affinity of Ag‐P&C NPs for bacteria, which can make Ag‐P&C NPs prone to target and penetrate into biofilms, and the self‐aggregated capacity helps Ag‐P&C NPs remain in biofilms for a long time to disrupt bacterial biofilm formation. In addition, biocompatible Ag‐P&C NPs are utilized in three types of bacteria‐infected animal models. They exhibit an excellent performance in killing bacteria, inhibiting plaque biofilms, and ameliorating inflammatory responses. In conclusion, this study offers new insights into antibiotic‐free antibacterial strategies, and exhibits promising application prospects. Abstract : Silver nanoparticles (Ag‐P&C NPs) with pH‐sensitive charge reversal and self‐aggregation capacities are successfully synthesized. In the acidic microenvironment of bacterial biofilms, protonation of the surface peptide enhances the affinity of Ag‐P&C NPs for bacteria. Whereafter the pH‐triggered self‐aggregated Ag‐P&C NPs remain in biofilms for a long time to disrupt bacterial biofilm formation.